Non-canonical Activities of Hog1 Control Sensitivity of Candida albicans to Killer Toxins From Debaryomyces hansenii - Morales-Menchén, Ana; Navarro-García, Federico; Guirao-Abad, José P.; Román, Elvira; Prieto, Daniel; Coman, Ioana V.; Pla, Jesús; Alonso-Monge, Rebeca (Frontiers in Cellular and Infection Microbiology, 2018)
Certain yeasts secrete peptides known as killer toxins or mycocins with a deleterious effect on sensitive yeasts or filamentous fungi, a common phenomenon in environmental species. In a recent work, different Debaryomyces hansenii (Dh) strains isolated from a wide variety of cheeses were identified as producing killer toxins active against Candida albicans and Candida tropicalis. We have analyzed the killer activity of these toxins in C. albicans mutants defective in MAPK signaling pathways and found that the lack of the MAPK Hog1 (but not Cek1 or Mkc1) renders cells hypersensitive to Dh mycocins while mutants lacking other upstream elements of the pathway behave as the wild type strain. Point mutations in the phosphorylation site (T174A-176F) or in the kinase domain (K52R) of HOG1 gene showed that both activities were relevant for the survival of C. albicans to Dh killer toxins. Moreover, Hog1 phosphorylation was also required to sense and adapt to osmotic and oxidative stress while the kinase activity was somehow dispensable. Although the addition of supernatant from the killer toxin- producing D. hansenii 242 strain (Dh-242) induced a slight intracellular increase in Reactive Oxygen Species (ROS), overexpression of cytosolic catalase did not protect C. albicans against this mycocin. This supernatant induced an increase in intracellular glycerol concentration suggesting that this toxin triggers an osmotic stress. We also provide evidence of a correlation between sensitivity to Dh-242 killer toxin and resistance to Congo red, suggesting cell wall specific alterations in sensitive strains.